Can quinoa (Chenopodium quinoa) replace traditional cereals under current climate scenarios? - Sun, Hongju; Khan, Waqas ud Din; Tanveer, Mohsin; Ijaz, Usman; Lu, Zhanyuan; Shabala, Sergey (Frontiers in Plant Science, 2025)
Agriculture is extremely vulnerable to climate change and crop production is severely hampered by climate extremes. Not only does it cost growers over US$170Bln in lost production, but it also has major implications for global food security. In this study, we argue that, under current climate scenarios, agriculture in the 21st century will become saline, severely limiting (or even making impossible) the use of traditional cereal crops for human caloric intake. As regaining the lost abiotic stress tolerance can only be achieved using modern gene editing technologies and given uncertainties on when and to what extent the public will embrace such new technologies, de novo domestication of already tolerant wild species or semi-domesticated “orphan” species is arguably the most efficient way to proceed. One of them is quinoa (Chenopodium quinoa), which is the focus of this review. Accordingly, we comprehensively evaluated the nutritional qualities of quinoa and discussed the benefits of using quinoa as a viable alternative to traditional cereals from both agronomical and nutritional points of view. We also highlight the existing gaps in the knowledge and the next steps required to ensure public acceptance of quinoa in a daily diet, alongside (or instead of) traditional cereals such as wheat or rice.